2009
DOI: 10.1016/j.ydbio.2008.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of olfactory placode development and neurogenesis is blocked in mice lacking both Six1 and Six4

Abstract: Mouse olfactory epithelium (OE) originates from ectodermally derived placode, the olfactory placode that arises at the anterior end of the neural plate. Tissue grafting and recombination experiments suggest that the placode is derived from a common preplacodal domain around the neural plate and its development is directed by signals arising from the underlying mesoderm and adjacent neuroectoderm. In mice, loss of Six1 affects OE morphogenesis but not placode formation. We show here that embryos lacking both Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 64 publications
2
84
0
Order By: Relevance
“…SIX1 expression level is increased in embryogenesis and promotes progenitor cell expansion and survival (6)(7)(8). SIX1 absence results in the reduction in size or loss of numerous organs, as a result of inhibited proliferation and increased apoptosis in mice (9). However, SIX1 expression is low in adult tissues, and aberrant expression of the SIX1 gene in adult tissue may contribute to carcinogenesis (10).…”
Section: Introductionmentioning
confidence: 99%
“…SIX1 expression level is increased in embryogenesis and promotes progenitor cell expansion and survival (6)(7)(8). SIX1 absence results in the reduction in size or loss of numerous organs, as a result of inhibited proliferation and increased apoptosis in mice (9). However, SIX1 expression is low in adult tissues, and aberrant expression of the SIX1 gene in adult tissue may contribute to carcinogenesis (10).…”
Section: Introductionmentioning
confidence: 99%
“…Six1 encodes a transcription factor and plays critical roles in the development of sensory organs (Zheng et al, 2003;Ozaki et al, 2004;Ikeda et al, 2007;Chen et al, 2009). We reported previously that Six1 is expressed in the OP and developing OE of mouse.…”
Section: Introductionmentioning
confidence: 99%
“…As we have previously found that loss of Six1 leads to abnormal cell death in the otic vesicle, the olfactory epithelium and in the pharyngeal endoderm-derived organs Zou et al, 2006;Chen et al, 2009), it is possible that a subpopulation of the…”
Section: Increased Apoptosis In the Developing Six1mentioning
confidence: 91%
“…Since the mutant mice contain a lacZ gene driven by the Six1 promoter, and the inserted lacZ transgene displayed a pattern identical to the Six1 mRNA distribution obtained by in situ hybridization (Chen et al, 2009;Laclef et al, 2003;Xu et al, 2003;Zheng et al, 2003), we stained for b-galactosidase activity in Six1 lacZ heterozygotes. Six1 expression was observed in the ureteral mesenchyme from ~E12.5 (Fig.…”
Section: Six1 Is Expressed In Ureteral Mesenchymementioning
confidence: 99%